1965
DOI: 10.1152/ajplegacy.1965.209.6.1199
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular transport of water, solute, and PAH in rats loaded with isotonic saline

Abstract: Renal tubular transport of water, osmotically active solute, and PAH were studied with micropuncture methods in anesthetized rats loaded with a volume of 0.9% sodium chloride solution equivalent to 10% of their body weight. Inulin clearance and urine flow were greatly elevated above values in nondiuretic animals, but there was little change in PAH clearance. F/P inulin-C14OOH ratios indicated that 42% of the filtered water and solute was reabsorbed along the proximal convolution, a lower fraction than is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
8

Year Published

1966
1966
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 0 publications
8
52
0
8
Order By: Relevance
“…In other studies in which whole kidney FF was compared with SNFF in normal rats (10,14), the former was measured by (19) found that less PAH appears in the final urine than is present in cortical distal tubules, a finding which we confirmed (10). This might mean that some PAH is reabsorbed in the collecting ducts.…”
Section: Filtration Fraction (Ff)supporting
confidence: 77%
“…In other studies in which whole kidney FF was compared with SNFF in normal rats (10,14), the former was measured by (19) found that less PAH appears in the final urine than is present in cortical distal tubules, a finding which we confirmed (10). This might mean that some PAH is reabsorbed in the collecting ducts.…”
Section: Filtration Fraction (Ff)supporting
confidence: 77%
“…Studies of TCH-o excretion in saline-loaded rats indicate that the sodium transport system in the ascending limb of the loop of Henle is unsaturable up to the highest rate of sodium delivery to the loop of Henle that can be-achieved in the intact animal (34). Cortney, Mylle, Lassiter, and Gottschalk (35) calculated from micropuncture studies that during hydropenia the proximal convolution of the rat nephron reabsorbed approximately three times as much sodium as the loop of Henle; the reabsorptive load per mass of tissue would therefore be roughly 8/3 as much in the loop as in the proximal convolution. During an infusion of isotonic saline, however, about 42% of the glomerular filtrate was reabsorbed in the proximal convolution and approximately the same amount in the loop.…”
Section: Methodsmentioning
confidence: 99%
“…No INTRODUCTION It is now well established that the increase in urinary excretion of sodium which occurs during acute saline loading is due to a decrease in sodium reabsorption by the tubules rather than to an increase in the amount of sodium filtered by the glomeruli (1)(2)(3)(4)(5)(6)(7)(8). The mechanism (or mechanisms) responsible for this decrease in tubular reabsorption is not entirely clear.…”
mentioning
confidence: 99%